Policy Network in the Process of Formulating the Qanun on Islamic Financial Institutions in Aceh - Muazzinah, Muazzinah; Zamharira, Cut; Khalil, Zakki Fuad; Wulandari, Dilya - (Department of Government Studies, Universitas Syiah Kuala, 2024)
The pros and cons of the implementation of Qanun Number 11 of 2018 concerning Islamic Financial Institutions among the people of Aceh are a strategic problem to be studied because this policy concerns economic activities in Aceh. Some people think that the existence of Islamic banks is not much different from conventional banks. Other people claim that the Aceh Government made a unilateral decision when it decided that all financial activities in Aceh must use sharia principles. However, many also agree with the existence of this Qanun, to save the people of Aceh from the practice of usury that has occurred in conventional banks. This study aims to examine the stages of policy formulation in the formulation of the Qanun on Islamic Institutions in Aceh and to find out what efforts have been made by the Aceh Government in involving actor networks at the stage of formulating the Qanun on Islamic Financial Institutions in Aceh. This type of research is descriptive qualitative with data collection techniques through FGD activities, interviews and document reviews. The results of this study indicate that based on the objective of implementing Islamic law in financial transactions in Aceh, this qanun was formulated, which began with the formation of a PANSUS, the preparation of an academic paper, so that in 2018 the Qanun LKS in Aceh was ratified. Meanwhile, at the actor network stage in the formulation of this Qanun LKS, the elements involved are still very limited, for example the absence of elements from entrepreneurs, civil society, and Dayah scholars.